Peningkatan Aksesibilitas Informasi Akademik Melalui Optimalisasi Web Jurusan dan Repositori Digital di Teknik Informatika UHO - Irwan Syahib, Muhammad; Rahman, La; Idris Putra, Muhammad; Setiawan , Adhi; Samsul, Samsul; Indra; Tapsil; Sadno, Muhammad (FAKULTAS TEKNIK UMKENDARI, 2026)
Stagnation in Tri Dharma data updates and limited access to academic documents on institutional websites can hinder campus bureaucratic efficiency and reduce the quality of public information services for the academic community. This community service activity aims to independently optimize the website of the Department of Informatics Engineering at Universitas Halu Oleo (UHO) as an integrated information hub and a digital document download center (repository). The implementation method comprises two main stages: inventorying and updating the latest Tri Dharma data content, and developing a download center feature based on a Content Management System (CMS). System functionality testing was conducted using the Blackbox Testing method to ensure the technical feasibility of downloading academic guidebooks, accreditation forms, and departmental administrative files. The results of the activity show that all digital repository features were successfully implemented with a 100% technical success rate. Based on the feedback survey conducted among the academic community as users, 51.4% of respondents strongly agreed that the new menu navigation structure has become neater, and 48.6% of respondents strongly agreed that academic information can now be accessed more quickly and efficiently. This activity has successfully transformed the department's information management toward an adaptive digital ecosystem.